2019
DOI: 10.1016/j.heliyon.2019.e02858
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of physical, mechanical and tribological properties of Al6061–ZrO2 nano-composites

Abstract: The present investigation mainly concentrates on work done in order to explore physical, mechanical & tribological characteristics of Al6061 alloy reinforced with nano-sized zirconium dioxide particulates. Four casts of different percentages of reinforcement from 0 to 6 wt% in the steps of 2 are fabricated using liquid metallurgy technique (stir casting). The prepared composites later subjected to various physical, mechanical & wear tests and results were studied. The tests were carried out in accordance with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 22 publications
(22 reference statements)
2
23
0
Order By: Relevance
“…The trend owes to many factors such as: (i) the surface deformation,(ii) removal of load bearing particles (ZrO2), (iii) increasing the friction due to the higher contacting couple surface and , faster generation , removal of the tribo-layer and rising the temperature of the surface with increasing the applied load, producing a soft surface. A similar result was obtained by many authors [15,30]. However, the wear resistance of the composites up to 10 wt.% of ZrO2 increases when compared with the base matrix.…”
Section: Effect Of Loadsupporting
confidence: 90%
See 1 more Smart Citation
“…The trend owes to many factors such as: (i) the surface deformation,(ii) removal of load bearing particles (ZrO2), (iii) increasing the friction due to the higher contacting couple surface and , faster generation , removal of the tribo-layer and rising the temperature of the surface with increasing the applied load, producing a soft surface. A similar result was obtained by many authors [15,30]. However, the wear resistance of the composites up to 10 wt.% of ZrO2 increases when compared with the base matrix.…”
Section: Effect Of Loadsupporting
confidence: 90%
“…Their outcomes showed the highest wear resistance was obtained with matrix has 3% ZrO2. Kumar et al [15] manufactured A6061/ZrO2 nano composite via stirring casting process. Wear test results showed that wear resistance of the MMCs improved as the content of nano-reinforcement increased.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the increase in the ZrO 2 reinforcement ratio in the composite structure led to gradual decrease in the wear losses. Similar results are reported in the studies in the literature (Ramachandra et al, 2015;Karthikeyan and Jinu, 2015a;Karthikeyan and Jinu, 2016;Madhusudhan et al, 2016;Pandiyarajan et al, 2017;Veeresh Kumar et al, 2019). In another study in the literature, it was stated that the oxide formed at the matrix-reinforcing interface plays an important role in reducing both the friction coefficient and the amount of wear (Karthikeyan and Jinu, 2015b).…”
Section: Effect Of Zro 2 Ratio On the Wearsupporting
confidence: 82%
“…Most of the research groups have investigated the properties of AMCs by incorporating (i) synthetic and (ii) natural reinforcement. Synthetic ceramic compounds such as SiO 2 [7], ZrO 2 [8], SiC [9], B 4 C [10], Al 2 O 3 [11], etc., as reinforcement have shown an excellent wear resistance of Alalloy matrix composites [12]- [14]. At the same time, natural minerals like rutile [15], garnet [16], zircon [17] etc.…”
Section: Introductionmentioning
confidence: 99%